Improvement in insulin resistance is greater when infliximab is added to methotrexate during intensive treatment of early rheumatoid arthritis—results from the IDEA study. (16th September 2016) - Bissell, Lesley-Anne; Hensor, Elizabeth M. A.; Kozera, Lukasz; Mackie, Sarah L.; Burska, Agata N.; Nam, Jacqueline L.; Keen, Helen; Villeneuve, Edith; Donica, Helena; Buch, Maya H.; Conaghan, Philip G.; Andrews, Jacqueline; et al.
Abstract : Objectives. To determine the change in established biomarkers of cardiovascular (CV) risk, namely, total cholesterol/high-density lipoprotein cholesterol ratio (TC/HDL-C), N-terminal pro-brain natriuretic peptide (NT-proBNP) and insulin resistance (IR) in patients with early RA treated with two different treat-to-target strategies. Methods. Fasting glucose, lipids, insulin and NT-proBNP were measured at baseline, weeks 26 and 78 in 79 DMARD-naïve RA patients, free of CV disease, as part of a double-blind randomized controlled trial of MTX with either infliximab (IFX) or methylprednisolone as induction therapy. Homeostasis model assessment–estimated IR (HOMA-IR) (glucose*insulin/405) was used to measure IR. Multiple imputation was employed, and linear regression analyses were adjusted for baseline values. Results. Changes in DAS44-CRP did not differ between the treatment arms at weeks 26 and 78. Mean TC/HDL-C, HOMA-IR and NT-proBNP improved in both groups at weeks 26 and 78, although change in NT-proBNP was not statistically significant at week 78. Changes in TC/HDL-C and NT-proBNP were similar between treatment arms, but HOMA-IR values in the IFX + MTX arm were 42% lower than those treated with MTX + methylprednisolone at week 78 (P = 0.003); the difference remained significant after adjustment for baseline BMI, ACPA positivity, smoking status and intramuscular glucocorticoid use (P = 0.007). Conclusion. When implementing a treat-to-target approach, treatment of early RA was associated with improvement in TC/HDL-C, HOMA-IR and NT-proBNP, and a greater long-term improvement in HOMA-IR was seen in those treated with IFX. Trial registration: EU Clinical Trials Register, http://www.clinicaltrialsregister.eu, Eudract-2005-005013-37; ISRTCNregisrty, http://www.isrctn.com, ISRCTN48638981